Costs analysis of integrating group interpersonal therapy into HIV care services in Senegal - Yao Abounan; Jérôme Wittwer; Judicaël Malick Tine; Ibrahima Ndiaye; Salaheddine Ziadeh; Sophie Desmonde; Hélène Font; Helen Verdeli; Ndeye Fatou Ngom; Nathalie de Rekeneire; Antoine Jaquet; Moussa Seydi; et al. (International Journal of Mental Health Systems)
Abstract Introduction Group Interpersonal Therapy (IPT), an evidence-based treatment of depression recommended by the WHO mhGAP Intervention Guide, was implemented through a task-shifting approach in Senegal, as a treatment for depressed people living with HIV (PLWH). Since a description of the resources used and the implementation costs incurred is necessary to inform policymakers better, this study aimed to estimate the costs associated with its implementation. Methods Intervention costs were analyzed using an “ingredients-based costing approach” from the provider’s perspective. We identified and described the start-up and implementation costs for the initial phase and a projection over 5 years (implementation at capacity). We estimated total annual costs and cost per beneficiary. We conducted a scenario analysis to highlight some cost uncertainties and their impacts. Results The total annual costs were estimated at $4064 for the initial phase and $8161 for the implementation at capacity. The training was the main cost driver representing approximately 60% of the total annual costs. The cost per beneficiary receiving group IPT was estimated at $65 for the implementation at capacity. The scenario analysis also illustrated the importance of parameters like the screening strategy, training activities, and allocation to cover transport costs mobilized by participants. Conclusion This cost analysis highlighted the costs and cost allocations required to implement group IPT in Senegal to treat depression in PLWH. This preliminary work should enable policymakers to identify the optimal resources to be mobilized to implement and ensure the sustainability of this therapy in HIV at a country-level program.